2022
DOI: 10.1038/s41598-022-12895-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved in-vivo airway gene transfer via magnetic-guidance, with protocol development informed by synchrotron imaging

Abstract: Gene vectors to treat cystic fibrosis lung disease should be targeted to the conducting airways, as peripheral lung transduction does not offer therapeutic benefit. Viral transduction efficiency is directly related to the vector residence time. However, delivered fluids such as gene vectors naturally spread to the alveoli during inspiration, and therapeutic particles of any form are rapidly cleared via mucociliary transit. Extending gene vector residence time within the conducting airways is important, but har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The ability to visualise the magnetic nanoparticles via their dark-field signal shows a significant advantage over the phase contrast imaging used by Donnelley et al (2022). The delivery image sequence shows that the magnetic particles are unexpectedly agglomerating or settling within the delivery tube for some reason, with the final 10% of the delivery period containing a substantially greater number of magnetic nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to visualise the magnetic nanoparticles via their dark-field signal shows a significant advantage over the phase contrast imaging used by Donnelley et al (2022). The delivery image sequence shows that the magnetic particles are unexpectedly agglomerating or settling within the delivery tube for some reason, with the final 10% of the delivery period containing a substantially greater number of magnetic nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Their motion within pulsatile blood vessel fluid can be modelled (Heidsieck et al 2012), but the non-stop, complex motion of the reversing air (breathing) and liquid (mucociliary clearance (Gardner et al 2020)) environment within the airway surface extends the challenges further. Simply visualising the magnetic nanoparticles to develop control mechanisms is difficult, however Donnelley et al (2022) have had some success using high-resolution x-ray imaging. That study utilised propagation-based phase-contrast effects to enhance image contrast, and showed that strings of magnetic nanoparticles formed in the airways of rats when a static external magnetic field was applied, similar to the strings that iron filings form under the influence of magnet fields.…”
Section: Introductionmentioning
confidence: 99%